Analisis Penerapan Etika Bisnis Islam pada Pelaku Usaha Mikro Kecil Menengah (UMKM) Muslim Makanan dan Minuman di Hamparan Perak - Dwi Febriyanthi; Siti Mujiatun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out how Muslim micro, small and medium enterprises (MSMEs) in the food and beverage sector apply Islamic business ethics. This research uses qualitative methods, especially descriptive with field studies. Data was collected through observations, books, journals and websites. The research results show that only three to four principles of Islamic business ethics are applied to Muslim MSMEs in the food and beverage sector in Hamparan Perak, while several other principles have not been implemented because economic actors do not understand Islamic business ethics.